Model Aplikasi Pemesanan Menu Pada Coffee Shop Can Ngopi - Andrew, Andrew; Kurniawan, Rido Dwi (STMIK Banjarbaru, 2026)
Manual ordering at Can Ngopi Coffee Shop often leads to communication errors and irregular queues, which necessitates the digitization of the service. This research aims to develop a website-based menu ordering application to improve operational efficiency. The system development used the Waterfall method, which encompasses the analysis, design, construction, and maintenance phases. Functionality validation was carried out through Black Box Testing. The test results showed that all the functionalities, such as the digital catalog and the shopping cart system, functioned effectively as required. The conclusion of the research confirms that this application effectively speeds up the transaction process, minimizes miscommunication between customers and staff, and facilitates management in monitoring sales reports in a structured manner.Keywords: Menu Ordering Application; Coffee Shop; Waterfall; Black Box Testing AbstrakPemesanan manual di Coffee Shop Can Ngopi sering memicu kesalahan komunikasi dan antrean tidak teratur, sehingga diperlukan digitalisasi layanan. Penelitian ini bertujuan membangun aplikasi pemesanan menu berbasis website untuk meningkatkan efisiensi operasional. Pengembangan sistem menggunakan metode Waterfall, meliputi tahap analisis, desain, konstruksi, hingga pemeliharaan. Validasi fungsionalitas fitur dilakukan melalui metode Black Box Testing. Hasil pengujian menunjukkan seluruh fitur, seperti katalog digital dan sistem keranjang, berjalan valid sesuai kebutuhan. Simpulan penelitian menegaskan bahwa aplikasi ini efektif mempercepat proses transaksi, meminimalisir miskomunikasi antara pelanggan dan staf, serta mempermudah manajemen dalam pemantauan laporan penjualan secara terstruktur. Kata kunci: Aplikasi Pemesanan Menu; Coffee Shop; Waterfall; Black Box Testing